Genome-wide identification, characterization, and expression analysis of the SOS1 gene family in the medicinal plant Paeonia ostii under salt stress - Chen, Yahong; Liang, Huabing; Wang, Zhanchang; Hussain, Quaid; Zhang, Xuexiong; Chen, Fazhi; Wang, Xiaohua (Frontiers in Plant Science, 2025)
Paeonia ostii is a commercially important ornamental and traditional medicinal plant esteemed in China. Salt stress is a widespread abiotic stress that significantly affects plant growth and development, and moderate stress can significantly promote the synthesis of plant secondary metabolites, requiring clarification of its underlying molecular mechanisms. The Salt Overly Sensitive 1 (SOS1) gene family is essential for salt stress tolerance, encoding Na+/H+ antiporters that preserve ion homeostasis and reduce cellular damage. This study conducted an extensive genome-wide analysis of the SOS1 gene family in Paeonia ostii, encompassing gene identification, characterization, three-dimensional and secondary structure prediction, gene structure and motif analysis, multiple alignments, phylogenetic tree construction, chromosomal localization, cis-regulatory element analysis, synteny analysis, Ka/Ks calculation, and gene expression analysis under salt stress treatments in three cultivars. Our findings identified 19 SOS1 genes within the P. ostii genome, demonstrating unique structural and functional attributes. All SOS1 genes were located on the plasma membrane and distributed across five chromosomes and two scaffolds. The conserved motif analysis results indicated that the SOS1 homologs had comparable protein structures. The coding sections of 19 PoSOS1 genes comprise amino acid sequences varying from 455 to 859, whereas the exons encompass amino acids ranging from 3 to 20. Furthermore, we discovered that the 2.5 kb upstream promoter region of the PoSOS1s gene has many cis-elements linked to phytohormones and stress responses. The phylogenetic study categorized the PoSOS1 genes into three subfamilies. In total, 38 miRNAs that target 19 PoSOS1 genes from 18 distinct families were identified. Conversely, gene expression analysis revealed six differentially expressed SOS1 genes in three distinct cultivars subjected to salt stress, with all six genes down-regulated and only one gene up-regulated in the QF-230 cultivar after six days of salt stress. This study offers new insights into the SOS1 gene family in P. ostii, elucidating its function in salt stress tolerance and establishing a foundation for future research on the functional characterization of SOS1 genes in P. ostii.